Darbinieku motivācija COVID-19 pandēmijas apstākļos - Funikovs, Jegors (Latvijas Universitāte, 2021)
Bakalaura darba pamatā ir šodienas COVID-19 problemātiskais jautājums. Bakalaura darbā tiek pētīta negatīva COVID-19 ietekme uz darbinieka motivāciju un produktivitāti. Bakalaura darba mērķis ir sniegt uzņēmumam noderīgus priekšlikumus, balstoties uz problēmas analīzi, izmantoto literatūru un autores veikto pētījumu rezultātiem. Bakalaura darba pētījuma rezultāti apstiprināja problēmas esamību. Pamatojoties uz datiem, kas saņemti no darbiniekiem un personāla speciālistiem, tiek secināts, ka COVID-19 graujoši ietekmē uzņēmuma darbinieku motivāciju.

The research work builds on the contemporary problem associated with COVID-19 today. The problem that is explored in the work is related to the fact that COVID-19 negatively affects the motivation of white-collar workers, as well as their productivity. The purpose of the author's work is to provide recommendations based on the analysis of the problem, the literature used, and the results of his own research, which could be useful for companies in solving the problem investigated by the author. The results of the research that were carried out in this scientific work confirmed the presence of this problem. According to employees, as well as HR specialists, COVID-19 really has a devastating effect on the motivation of company employees.
Employee’s Motivation during COVID-19 pandemic
Keywords: Ekonomika un uzņēmējdarbība; human resource management; employee’s motivation; COVID-19 effects; remote work; teleworking